EFEKTIVITAS BANTUAN SOSIAL BAGI EKS WTS SOCIAL ASSISTANCE ACTIVITIES FOR WTS EXCLUSIONS - Listyawati Listyawati Listyawati (Media Informasi Penelitian Kesejahteraan Sosial, 2020)
Abstrak        This type of evaluation research with a survey approach model, the selection of respondents determined by random technique, as many as 30 ex-WTS from a number of ex-WTS populations who were returned to the area of origin. Main data collection: with interview and free observation techniques. Data analysis: using a combination of descriptive-quantitative and descriptive-qualitative techniques. Research objectives: 1) Knowing the scheme model and localization closure pathway involving the Ministry of Social Affairs and local government from an empirical research base on the closure of localization that has been carried out. 2) The living conditions of ex-WTS in the area of origin are known, especially in utilizing assistance provided by the government and the extent of the effectiveness of social assistance for ex-WTS in the place of origin. 3) Known impacts experienced by parties related to the existence of localization at the study site.                    Results of the study 1) Schematic model and planned closure localization model because there is no standard rule. 2) Stimulant assistance is 36.67% effective, 43.33% less effective stimulant assistance, and only 20% effective stimulant assistance. 3) The impact on the parties related to the existence of localization is that most of the income is decreasing and some is losing work. Optimizing policy recommendations aimed at: 1) Ministry of Social Affairs through the Directorate: Creating a clear schema model and flowchart; Increase business capital assistance and synergize with local governments; Transport money for returning WTS to their original home needs to be reviewed. 2. Local Government: Increase (budget support, monitoring and evaluation); Careful planning; Adequate time technical guidance; Mentoring more intensity; The policy of closing localization with the transfer of functions as a coffee shop and karaoke place is very high risk for the misuse of prostitution. The alternative is that the building is used by other activities that are not vulnerable to prostitution, or totally closed. For parties related to the existence of localization which is affected by the closure of localization, by providing skills and business capital to get new businesses, so as not to add to social problems.Keywords: Effectiveness, Social Assistance, Ex-WTSAbstrakJenis penelitian evaluasi dengan model pendekatan survei,pemilihan responden ditentukan dengan teknik random, sebanyak 30 eks WTS  dari sejumlah populasi eks WTS yang dipulangkan ke daerah asal. Pengumpulan data utama: dengan teknik wawancara dan observasi bebas. Analisis data: mengunakan teknik gabungan deskriptif-kuantitatif dan deskriptif-kualitatif. Tujuan penlitian: 1) Diketahuinya model skema dan alur penutupan lokalisasi yang melibatkan Kementerian Sosial dan pemerintah daerah dari basis penelitian empirik tentang penutupan lokalisasi yang telah dilakukan. 2) Diketahui kondisi kehidupan eks WTS di daerah asal terutama dalam memanfaatkan bantuan yang diberikan oleh pemerintah dan sejauhmana efektivitas bantuan sosial bagi eks WTS di tempat asal. 3) Diketahui dampak yang dialami pihak-pihak yang berkait dengan eksistensi lokalisasi di lokasi penelitian.Hasil penelitian 1) Model skema dan alur penutupan lokalisasi model yang direncanakan karena belum ada atuan yang baku. 2) Bantuan stimulan cukup efektif 36,67%, bantuan stimulan kurang efektif 43,33%, dan bantuan stimulan efektif hanya 20%. 3) Dampak bagi pihak terkait dengan eksistensi lokalisasi sebagian besar penghasilan menurun dan sebagian  kehilangngan pekerjaan. Optimalisasi kebijakan rekomendasi ditujukan kepada: 1) Kementerian Sosial melalui Direktorat:  Membuat model skema dan alur pikir yang jelas; Meningkatkan bantuan modal usaha dan bersinergi dengan pemerintah daerah; Uang transport pemulangan WTS ke rumah asal perlu dikaji lagi. 2. Pemerintah Daerah: Meningkatkan ( dukungan anggaran, monitoring dan evaaluasi); Perencanaan yang matang; Bimbingan teknis waktu yang cukup; Pendampingan lebih intensitas; Kebijakan penutupan lokalisasi dengan alihfungsi sebagai warung kopi dan tempat karaoke sangat berisiko tinggi untuk disalahgunakan praktek prostitusi. Alternatifnya adalah gedung tersebut dimanfatkan kegiatan lain yang tidak rentan terhadap kegiatan prostitusi, atau ditutup total. Bagi pihak terkait dengan eksisstensi lokalisasi yang terkena dampak penutupan lokalisasi, dengan memberikan bekal keterampilan dan modal usaha guna mendapatkan usaha baru, sehingga tidak menambah permasalahan sosial.Kata kunci: Efektifvitas, Bantuan Sosial,Eks WTS.